2021
DOI: 10.1371/journal.pone.0251149
|View full text |Cite
|
Sign up to set email alerts
|

A robust method of nuclei isolation for single-cell RNA sequencing of solid tissues from the plant genus Populus

Abstract: Single-cell transcriptome analysis has been extensively applied in humans and animal models to uncover gene expression heterogeneity between the different cell types of a tissue or an organ. It demonstrated its capability to discover key regulatory elements that determine cell fate during developmental programs. Single-cell analysis requires the isolation and labeling of the messenger RNA (mRNA) derived from each cell. These challenges were primarily addressed in mammals by developing microfluidic-based approa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
(49 reference statements)
0
28
0
Order By: Relevance
“…We show that the isolation and analysis of individual nuclei result in the detection of diverse cell types and numbers of transcripts to enable their discrimination at a resolution comparable with whole cells in plants. Moreover, we demonstrated that this procedure can be applied to lignified Populus stems (13). The reported transcriptomes of shoot apex procambial cells, in combination with the feasibility of our nuclei isolation protocol to explore the single-cell transcriptomic in the stem, constitute an unpreceded opportunity to dissect the missing link between primary and secondary growth, including how cambium develops from procambium at the initiation of secondary growth.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…We show that the isolation and analysis of individual nuclei result in the detection of diverse cell types and numbers of transcripts to enable their discrimination at a resolution comparable with whole cells in plants. Moreover, we demonstrated that this procedure can be applied to lignified Populus stems (13). The reported transcriptomes of shoot apex procambial cells, in combination with the feasibility of our nuclei isolation protocol to explore the single-cell transcriptomic in the stem, constitute an unpreceded opportunity to dissect the missing link between primary and secondary growth, including how cambium develops from procambium at the initiation of secondary growth.…”
Section: Discussionmentioning
confidence: 95%
“…We harvested 20 shoot apices from 3-weeks-old in vitro grown hybrid poplar (Populus tremula × alba) plants and performed high-throughput, microfluidic-based single-nuclei RNA sequencing (snRNA-seq) using the 10× Genomics Chromium technology as we described previously (13). For all quality control and analytical steps, we used Asc-Seurat (14), a comprehensive web application that encapsulates a series of tools for scRNA-seq data analysis.…”
Section: An Atlas Of Populus Vegetative Shoot Apex Cellsmentioning
confidence: 99%
See 3 more Smart Citations